A Case Study of Psoriasis Vulgaris After COVID-19 Vaccination in Saudi Arabia - Alwafi, Hassan; Alsulaimani, Nedaa; Almalki, Mohammed E.; Banjar, Asma Mohammad; Alamri, Reham Abdullah; Alwafi, Danya; Jarab, Anan S.; El-Qasem, Asaleh; Alhartani, Yosra J.; Naser, Abdallah Y (Majalah Kedokteran Bandung, 2025)
Since the COVID-19 vaccines have been approved, worldwide reports of adverse events have been reported. Although a few cases of Psoriasis vulgaris have been reported after COVID-10 vaccination, there is currently limited evidence to establish a direct relationship between the vaccine and this condition. A 27-year-old Saudi woman, previously healthy and had no medical issues, reported skin lesions on her lower legs, which she noticed ten (10) days after receiving the first dose of the Pfizer COVID-19 vaccine. The patient had no prior history of such lesions or any family history of psoriasis. Joint pain was not observed. A diagnosis of psoriasis vulgaris was made, and the patient was treated with Daivobet® cream, urea cream 10%, and full-body NB-UVB light therapy three times a week for up to two months. The patient's condition improved partially. This report presents the first known case of psoriasis vulgaris after the COVID-19 vaccine in the Middle East. Further research is needed to fully understand this connection. The study emphasizes the significance of a thorough medical history and evaluation for precise diagnosis and treatment.